Alterations in Preterm Brain Development: Relation to Developmental Assessment and Prediction - Aylward, Glen P. (American Journal of Perinatology, 2023)
Infants born extremely preterm are at risk for compromised cognitive and motor outcome. There are various possibilities as to why this occurs. The “two-hit” hypothesis consists of interrelated developmental disruptions and insults. Both specifically affect the transient subplate neuronal layer (SNL) and the early development of brain circuitry. The SNL, analogous to a switchboard, is critical in connecting cortical and lower brain centers and is highly susceptible to disruptions and insults, producing dysfunctional neural networks. Damage to the SNL provides the putative link between atypical early brain development and later cognitive and academic function that require complex neural circuitry. This, in turn, has major ramifications for developmental assessment and prediction.Key Points
Keywords: subplate neurons; brain circuits; preterm; infant assessment; prediction